Impact on Corporate Social Responsibility on Brand Loyalty: Examining Mediating Impact of Brand Trust: with Reference to Food and Beverage Industry - Kaushan, K. R. U.; Medis, Ajith (Department of Marketing Management, Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2021)
The food and Beverage Industry is always an emerging industry in Sri Lanka. This study was conducted to examine the impact of corporate social responsibility on brand loyalty and the relationship between corporate social responsibility and brand trust, and finally, the relationship between brand love and brand trust. However, this study concentrated on three corporate social responsibility dimensions: corporate legal responsibility, Corporate ethical responsibility, and Philanthropic responsibility. These have been selected as dimensions of the study's independent variable. Using a quantitative research approach, this study was conducted and used a survey questionnaire to collect primary data. The researcher will be used a quantitative research design, and the actual data collected will be analyzed using a statistical package for social science (SPSS) version 26. To test the developed hypotheses, correlation analysis and linear regression analysis were used. The study revealed that there is a significant relationship between corporate social responsibility and brand loyalty. Furthermore, there is a significant relationship between corporate social responsibility and brand trust and a significant relationship between brand trust and brand loyalty. This study is only catering to the food and beverage industry I suggest doing the other contexts. Through this research, organizations can identify fulfilling brand loyalty to increase the organization's profits and increase the social consumption quality.
Keywords: Brand Loyalty, Brand Trust, Corporate Social Responsibility